Community and Individual Causes of Students Failure in Al Kindy College of Medicine 2012 - Ibrahim, Mohammed Asaad (AL-Kindy College Medical Journal, 2013)
Bac kground:Failure is the state or condition of not meeting a desirable or intended objective, and may be viewed as the opposite of success; students always have a question "Why did I get this grade. On the contrary success leads towards new sources of earning, in fact there are a lot of interacting factors play such extrinsic and extrinsic to reach success.Objec t i ves :To explore internal and external factors causing students failure in medical college and to reconnoiter factors improve academic performance.Methods: A cross-sectional study, conducted in Al Kindy College of Medicine, for the period from November 8th 2012 to May 1st 2013. Formal ethical considerations were obtained about participation and methodology. A sample of 152 students were included and classified according to their year in the college, a questionnaires about students opinion, include a lot of factors in the all fields of educational process and socio-demographic linked with final outcome of the students.Resul t s : success was more in females, fifth year (83%), student wellness (78%), practical teaching method (75%), regularity in attendees (80%), all lecture attendees (85%), 3-5 family number (78%), 6-10 studying hours (82%), and 25 reading hours weekly (100%), also result of student opinion about crowded weekly schedule (80%), daily quizzes influence (76%), comprehensive material (85%), long lecture duration (74%), headache as cause of failure (23%), consult doctors if there is health problem (88%), and internet uses (72%). These result come in consistent with international studies and researches.Conc lus ions : applying new techniques in medical education good health monitoring can improve students' academic outcome.